Informal taxation in Sierra Leone: Magnitudes, perceptions and implications. Issue 471 (24th October 2018) - van den Boogaard, Vanessa; Prichard, Wilson; Jibao, Samuel
Abstract: In low-income countries, citizens often pay 'taxes' that differ substantially from what is required by statute. These non-statutory taxes are central to financing both local public goods and maintaining informal governance institutions. This study captures the incidence of informal taxation and taxpayer perspectives on these payments. We find, first, that informal taxes are a prevalent reality within areas of weak formal statehood in Sierra Leone, with households paying an equal number of informal and formal taxes. Second, we find positive taxpayer perceptions of the fairness of informal taxes relative to formal taxes, despite informal taxes being regressive in their distribution. We explain this by the fact that taxpayers are more likely to trust the actor levying these payments and are more likely to believe that they will be used to deliver benefits to the community.